Автоматизация проектирования тепловых пунктов системы централизованного теплоснабжения - Хавин, Валерий Львович; Арсеньева, Ольга Петровна; Мацегора, Александр Иванович; Кусаков, Сергей Константинович; Бочарников, Игорь Александрович; Василенко, Александр Анатольевич (Национальный технический университет "Харьковский политехнический институт", 2016)
Розроблено автоматизовану систему проектування теплових пунктів на основі пластинчатих теплообмінників. Представлено їх класифікацію за встановленим обладнанням. Надана номенклатура системи управління роботою теплового пункту та допоміжного обладнання.

The automated system of designing heating points based on plate heat exchangers is developed. Their classification according to the installed basic equipment is submitted. The nomenclature of the operation control system and substation accessories is adduced.
Automation design of heat point for district heating system
Keywords: энергосберегающие проекты; энергоносители; рост цен; энергетический кризис; тепловая энергия; распределение; потребление; горячее водоснабжение; потеря тепла; пластинчатые теплообменные аппараты